2023
DOI: 10.1038/s41598-023-29230-7
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in plant disease severity assessment using convolutional neural networks

Abstract: In modern agricultural production, the severity of diseases is an important factor that directly affects the yield and quality of plants. In order to effectively monitor and control the entire production process of plants, not only the type of disease, but also the severity of the disease must be clarified. In recent years, deep learning for plant disease species identification has been widely used. In particular, the application of convolutional neural network (CNN) to plant disease images has made breakthrou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 76 publications
0
13
0
1
Order By: Relevance
“…Shi et al ( 2023 ) reported that there are relatively few studies on disease severity assessment; thus, their aim is to tracing prevailing views of existing studies in order to provide its grading criteria. They also addressed the main obstacles that CNN-based plant disease severity assessment systems confront in practical applications and gave plausible research ideas and potential ways to address them.…”
Section: Review Of Related Workmentioning
confidence: 99%
“…Shi et al ( 2023 ) reported that there are relatively few studies on disease severity assessment; thus, their aim is to tracing prevailing views of existing studies in order to provide its grading criteria. They also addressed the main obstacles that CNN-based plant disease severity assessment systems confront in practical applications and gave plausible research ideas and potential ways to address them.…”
Section: Review Of Related Workmentioning
confidence: 99%
“…Viral proteins involved in replication can phase separate to drive the formation of viral compartments [44]. α-Crystallin can form condensates through LLPS upon stimulation by several risk factors, such as ageing and diabetes, contributing to cataracts [45].…”
Section: Aberrant Llps May Be Involved In Disease Pathologymentioning
confidence: 99%
“…It is indicated that Leaf Doctor is one program that, in subsequent upgrades, will employ the suggested methodology. Shi et al [39] outlined different studies on convolution neural network (CNN) based plant disease severity assessment in terms of classical CNN frameworks, improved CNN architectures, and CNN based segmentation networks, depending on the network architecture. The study also provided a detailed comparative analysis of the advantages and disadvantages of each approach.…”
Section: Literature Reviewmentioning
confidence: 99%